How Do Off-Season Cover Crops Affect Soybean Weed Communities? - Eduarda Grün; Alexandre Ferigolo Alves; Anelise Lencina da Silva; Alencar Junior Zanon; Arícia Ritter Corrêa; Eduard Mroginski Leichtweis; Roberto Costa Avila Neto; André da Rosa Ulguim (Agriculture)
Weeds compete for environmental resources, leading to reduced soybean yield. In this context, integrated weed management strategies related to cultural control with the use of cover crops are necessary. Our aim was to evaluate weed occurrence in soybean systems with different cover crops. Field studies were conducted at Júlio de Castilhos, Santa Maria, Capão do Leão, Barra do Ribeiro, and Santo Ângelo, Rio Grande do Sul, Brazil. A randomized complete block design with four replications was used. Treatments consisted of black oats (Avena strigosa Schreb.), white oats (Avena sativa L.), rye (Secale cereale L.), hairy vetch (Vicia sativa L.), forage turnip (Raphanus sativus L.), and white clover (Trifolium repens L.) in pure stands or in mixtures. The analyzed variables were relative frequency, density, abundance, and importance value index, similarity index of weeds, dry shoot mass of cover crop, and soybean yield. Cover crops containing white or black oats reduced the relative importance value index of weeds, such as Lollium multiforum, Conyza spp., and Bidens pilosa. Forage turnip, hairy vetch, and white clover showed distinct responses. Black oats and forage turnip did not differ from cover crop mixtures in terms of dry shoot mass and grain yield, being superior to fallow, white clover, and hairy vetch.